Penerapan Prinsip Good Corporate Governance pada Kinerja Berbasis Balanced Scorecard di LPD Kabupaten Badung - Dewi, Made Yunita Chandra; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2020)
Good corporate governance (GCG) is a system to regulate the structure and mechanism so that it can drive the efficiency and performance of the company. This study aims to determine the effect of GCG on the performance of the balanced scorecard based on the LPD in Badung. Proxies used are GCG principles consisting of transparency, accountability, responsibility, independence and fairness. Sampl  are 72 LPD in Badung. primary data with questionnaires are used and analyzed by multiple regression. The results indicate that the application of the principle of responsibility has a significant effect, while the principles of transparency, accountability, independence, and reasonableness do not have a significant effect on performance based on the Balanced Scorecard. Keywords: Good Corporate Governance Principles; Performance Based Balanced Scorecard.